2012
DOI: 10.12991/201216401
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against acrylamideinduced oxidative tissue damage in rats

Abstract: INTRODUCTION Acrylamide (CH 2 =CHCONH 2 ) is an , -unsaturated carbonyl compound with a significantly high chemical activity (1). It is extensively used mainly in the manufacture of water-soluble polymers. These polymers are primarily employed by the wastewater, paper, mining, and oil industry (2). ACR does not occur naturally. It was found in various fried, deep-fried and oven-baked foods. It occurs in foods that are regularly consumed throughout the years, not only crisps and bread, but also biscuits, cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…TA transversions. Our results showed that 8-OHdG level in the ACR-treated group significantly increased compared with the control group, which is in agreement with the findings of Tozan-Beceren et al (2012). In the present study, increases in MDA, PC and 8-OHdG levels induced by ACR were prevented by quercetin treatment demonstrating that ACR caused oxidative organ injury in the liver, brain, testes and kidney tissues were Values are expressed as means 6 SEM (n 5 10).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…TA transversions. Our results showed that 8-OHdG level in the ACR-treated group significantly increased compared with the control group, which is in agreement with the findings of Tozan-Beceren et al (2012). In the present study, increases in MDA, PC and 8-OHdG levels induced by ACR were prevented by quercetin treatment demonstrating that ACR caused oxidative organ injury in the liver, brain, testes and kidney tissues were Values are expressed as means 6 SEM (n 5 10).…”
Section: Resultssupporting
confidence: 91%
“…Glutathione is a cysteine-containing tripeptide that plays a critical role in the protection of tissues by directly interacting with ROS as well as an important component in the metabolism of many xenobiotics, like ACR (Kurebayashi and Ohno, 2006;Siu et al 2013). It has been demonstrated that ACR caused depletion of GSH content (Tozan-Beceren et al 2012), which is in agreement with our results. Quercetin has been found to increase the expression of c-glutamylcysteine synthetase with a concomitant increase in the intracellular glutathione concentrations (Moskaug et al 2005).…”
Section: Acrylamide-induced Oxidative Stress In Ratssupporting
confidence: 92%
“…Disturbances in the normal redox state by ACY can cause toxic effects through the production of cell damaging peroxides and free radicals. A decline in serum TAC coincided with the results obtained by Tozan-Beceren et al (2012).…”
Section: Discussionsupporting
confidence: 86%
“…The supposition that supplementation with a high dose of inositol to the extender decreased DNA damage was assessed by using 8-OHdG after freezing and thawing. Previous study results showed that acrylamide treatment resulted in a high plasma level of 8-OHdG, which was decreased when rats were treated with melatonin [ 76 ]. Similarly, Governini et al [ 54 ] measured the level of 8-OHdG in treated and untreated sperm with MI (20 mg/mL) to evaluate the ability of MI to prevent DNA damage.…”
Section: Discussionmentioning
confidence: 99%